JOÃO PESSOA CITY – PB TERRITORIAL ANALYSIS: ENVIRONMENTAL, SOCIAL AND HEALTH PROBLEMS (Fiep Bulletin - online, 2013)
Objective: identify the situation of João Pessoa-PB regarding to local population environment, social and health determinants problems. Methodology: The authors conducted exploratory research, descriptive bibliographical and documentary. Data were collected between August and October 2011 and were consulted websites and official files. Results: João Pessoa has experienced serious problems, such as saturation of infrastructure, and water pollution, social stratification, peripherization population, urban violence, and other income concentration. Conclusion: knowing that profile is extremely relevant, since it is possible to promote strategies for the promotion of health and prevention, indispensable attributes for the new proposed health intervention in the country, assisting in the performance of Primary Health with quality, equity and universality.
Keywords: Territory. João Pessoa; Problems; Health Promotion.